Performance and environmental life cycle analysis of thermosyphon solar water heaters - Kalogirou, Soteris A. (My University, 2004)
One of the most widely used systems for domestic water heating is the solar thermosyphon unit. A thermosyphon system, suitable for Mali, consists of one flat-plate collector panel 1.35m2 in aperture area and a 150 lt hot water cylinder. No pump is required for this system as the hot water is transferred to storage because of the thermosyphon effect. The system is modeled and simulated with TRNSYS program for Bamako, Mali and the results show that 6,648 MJ of energy can be provided per year and the solar contribution is 0.96, i.e., 96% of the needs for hot water for a 4-6 persons family are satisfied with solar energy. The financial characteristics of the system investigated give positive and very promising figures. By considering a rate for electricity equal to 0.16 US$/kWh, the pay back time is 2 years and the life cycle savings, representing the money saved because of the use of the system throughout its life (20 years) instead of using conventional energy (electricity), is US$ 2,200. With respect to the life cycle assessment, the pollution created for the production of the system is estimated by calculating the embodied energy invested in the manufacture, assembly and installation of the collectors and other parts of the system. For the present thermosyphon system the embodied energy is found to be equal to 4,283 MJ. By considering the useful energy collected by the system each year, the embodied energy is recouped in about 8 months. It can therefore be concluded that solar energy systems offer significant protection to the environment and cost savings and should be employed whenever possible in order to achieve a sustainable future.